COMPARING EARLY MALADAPTIVE SCHEMAS AND QUALITY OF LIFE AMONG ADDICTED AND NON-ADDICTED ADOLESCENTS - Noshaba Razaq; Shaista Akmal; Muhammad Akmal; Abdulmohsen Bakhsh; Qurrat-ul-ain; Majid Malik (International Journal of Contemporary Issues in Social Sciences, 2024)
Objectives: To compare, early maladaptive schemas and quality of life among addicted and non-addicted adolescents. Methodology: This Correlational study was conducted on addicts’ and non-addicts adolescents from March 2021 to December 2021. Sample of the current study was comprised of 352 addicts’ and non-addicts adolescents. The sample was purposefully selected from hospitals and clinics of Rawalpindi Islamabad Pakistan. The questionnaires, Urdu version of YSQ-SF assessing early maladaptive schema and Urdu version of WHOQOL- BREF assessing quality of life were used to compare early maladaptive schemas and quality of life among addicts and non-addicts. Result: Addicts score for early maladaptive schema (M =348.58, SD =22.71), and non-addicts score for early maladaptive schema (M =117.43, SD =17.32), while addicts score for Quality of life (M =49.11, SD =15.69), and non-addicts score for Quality of life (M =168.43, SD =34.55).Moreover study results showing that early maladaptive schema (β = -13.8887, p ≥ .05) has negative influence on quality of life of adolescent. Conclusion: The results of study concluded that early maladaptive schema has negative influence on quality of life of adolescents and addicts showing greater early maladaptive schema and poor quality of life as compared to non-addicts.